PACMEL: A phase 1 dose escalation trial of trametinib (GSK1120212) in combination with paclitaxel. Issue 3 (February 2015) - Coupe, Nicholas; Corrie, Pippa; Hategan, Mirela; Larkin, James; Gore, Martin; Gupta, Avinash; Wise, Adelyn; Suter, Sam; Ciria, Cristian; Love, Sharon; Collins, Linda; Middleton, Mark R.
Abstract Background We sought to determine the maximal tolerated dose of the MEK inhibitor trametinib with weekly paclitaxel, with a view to exploring the combination's activity in melanoma lacking a BRAF V600 mutation. Methods In this phase 1 study we used a fixed dose of paclitaxel (80 mg/m2 intravenous (IV) on days 1, 8 and 15 of each 4 week cycle) and escalated the dose of trametinib (to a maximum 2 mg orally (PO) daily), following a 3 + 3 design. Eligible patients had advanced melanoma and could have received up to two previous lines of treatment for metastatic disease. Findings 15 patients were enrolled, all but one of whose melanoma was wild type for BRAF at codon 600. The maximal monotherapy dose of trametinib proved tolerable with weekly paclitaxel. The most frequent adverse events observed were rash and fatigue. Six (40%) partial responses were reported, including four of eight patients with NRAS mutations. Median progression free survival was 5.5 months (95% confidence interval (CI) 1.8–7.8 months) and overall survival, 14.1 months (95% CI 4.6–not reached). Interpretation Trametinib can safely be given with weekly paclitaxel at the full monotherapy dose. In this small group promising progression free and overall survival were observed in patients with melanoma lacking a V600 BRAF mutation.